The involvement of physician assistants in inpatient care in hospitals in the Netherlands: a cost-effectiveness analysis - Timmermans, Marijke J.C.; Wensing, Michel (BMJ open, 2017)
Objective: To investigate the cost-effectiveness of substitution of inpatient care from medical doctors (MDs) to physician assistants (PAs). Design: Cost-effectiveness analysis embedded within a multicentre, matched-controlled study. The traditional model in which only MDs are employed for inpatient care (MD model) was compared with a mixed model in which, besides MDs, PAs are also employed (PA/MD model). Setting: 34 hospital wards across the Netherlands. Participants: 2292 patients were followed from admission until 1 month after discharge. Patients receiving daycare, terminally ill patients and children were excluded. Primary and secondary outcome measures: All direct healthcare costs from day of admission until 1 month after discharge. Health outcome concerned quality-adjusted life years (QALYs), which was measured with the EuroQol five dimensions questionnaire (EQ-5D). Results: We found no significant difference for QALY gain (+0.02, 95% CI −0.01 to 0.05) when comparing the PA/MD model with the MD model. Total costs per patient did not significantly differ between the groups (+€568, 95% CI −€254 to €1391, p=0.175). Regarding the costs per item, a difference of €309 per patient (95% CI €29 to €588, p=0.030) was found in favour of the MD model regarding length of stay. Personnel costs per patient for the provider who is primarily responsible for medical care on the ward were lower on the wards in the PA/MD model (−€11, 95% CI −€16 to −€6, p<0.01). Conclusions: This study suggests that the cost-effectiveness on wards managed by PAs, in collaboration with MDs, is similar to the care on wards with traditional house staffing. The involvement of PAs may reduce personnel costs, but not overall healthcare costs.
Gesehen am 07.06.2018